Peste des petits ruminants: past, present, and future scope - Fayyad, Adnan F; Alzuheir, Ibrahim M (The Journal of Infection in Developing Countries, 2024)
Introduction: Peste des petits ruminants (PPR) is a highly contagious and fatal disease affecting small ruminants, particularly goats and sheep, and is caused by Morbillivirus caprinae, a virus in the genus Morbillivirus, family Paramyxoviridae. PPR has significant economic and social impacts, especially in Africa, Asia, and the Middle East, where small ruminants are vital to rural livelihoods and food security. This disease is a priority for global eradication due to its disproportionate impact on low-income farmers and wildlife conservation. Methodology: A literature review was conducted to capture recent information on the epidemiology, diagnosis, host range, transmission, pathogenesis, economic impact, vaccination strategies, and eradication efforts for PPR. This review also explores future perspectives to address gaps in the current understanding and control of the disease. Results: The review highlights that PPR remains a severe challenge in low-resource areas, causing notable economic loss and endangering wildlife. Vaccination efforts have shown effectiveness, though limited accessibility and high costs persist as barriers. The disease has gained attention from international organizations aiming for global eradication by 2030, with ongoing advancements in diagnostics and surveillance methods showing promise in control efforts. Conclusions: This review underscores recent advancements in PPR research, focusing on disease distribution, diagnostic improvements, and control strategies. These findings are valuable for regional and global eradication initiatives, providing a foundation for policies that support sustainable livestock economies and biodiversity conservation. International collaboration, effective vaccination programs, and strategic surveillance are essential to achieve the 2030 eradication goal and secure the health of vulnerable livestock populations.